Defect sensitivity to failure of highly deformable polymeric materials. (April 2017) - Brighenti, Roberto; Carpinteri, Andrea; Artoni, Federico
Highlights: Failure defect sensitivity in polymers is examined. A theoretical mechanical model is formulated based on entropy concept. A theoretical failure mechanism of polymers is taken into account. Failure experimental results of notched sheets are presented. Experimental results are compared with numerical outcomes. Abstract: The capability of materials to bear loads even in presence of defects like cracks, notches or generic geometric discontinuities is usually indicated as flaw tolerance, and is crucial in modern safety design of structural components. Such a tolerance capability can be remarkable in highly deformable materials (also called soft materials), usually much more pronounced than in conventional ones. The ability of highly deformable materials to undergo very large deformations before failure is mainly due to their noticeable rearrangement of the molecular network with a significant decrease of the internal entropic state. Neglecting such an entropic effect can lead to erroneous underestimations of the safety level against defect-driven failure. In the present research, the mechanics of highly deformable materials is discussed by examining silicone-based notched and cracked plates. Experimental, numerical and theoretical aspects of the involved phenomena are analyzed in order to provide an explanation of the mechanism of defect resistance in such a class of materials from a physics-based point-of-view.